Reaching the 6-hour target: a comparative analysis of patient characteristics and outcomes in the emergency department (UCC Student Medical Journal, 2026)
Objectives: Prolonged Emergency Department (ED) visits lead to overcrowding, compromising safe provision of care. To improve patient outcomes, the Emergency Medicine Programme for Ireland set a national target that 95% of ED attendees should be admitted or discharged within 6 hours. This study aims to define the characteristics of patients attending the ED and compare these characteristics for patients whose episode of care was or was not concluded within the 6-hour target.Methods: A cross-sectional study was conducted at Cork University Hospital (CUH), a level one major trauma centre. A total of 2,166 adult patients (aged >= 16 years) were included from the iPatient Manager database.Results: Overall, 50.9% (n = 1,103) of patients had an episode of care lasting less than 6 hours. Over 75s were more likely to stay over 6 hours (n = 300, 68%). The most frequent presenting complaints were ‘limb problems’ (n = 218, 69%) under 6 hours and ‘shortness of breath’ (n = 73, 66%) over 6 hours. Most episodes of care concluded under 6 hours for self referrals and over 6 hours for 999 calls and GP referrals. Triage categories 1, 4 or 5 were more likely to stay in ED under 6 hours. Admitted patients were more likely to stay in ED over 6 hours (n = 606, 74%).Conclusion: This study suggests national targets are not being met, indicating the need for better streamlined outpatient services and further resourcing for urgent care service planning and provision in the future.